Remarks on the sexual dimorphism and taxonomy of Fabia Dana, 1851 (Crustacea, Brachyura, Pinnotheridae) - Campos, Ernesto (Zootaxa, 2013)
A study of the holotype of Pinnotheres hemphilli Rathbun, 1918, revealed it is an early post-hard female, not a male, of Fabia Dana, 1851. The morphology of Pinnotheres emiliai Melo, 1971 (based on a male specimen) and Fabia insularis Melo, 1971 (based on a female specimen) confirm earlier hypothesis that they belong to a sexually dimorphic species that should be known as F. emiliai (Melo, 1971). The redescription of the holotype of Fabia felderi Gore, 1986, supports its generic assignment and its relationship with F. emiliai. The implication of sexual dimorphism and intersexes in the taxon-omy of Fabia is discussed.